Mapping the future: The current landscape and future directions of evidence-based practice in Saudi radiology departments. - Walaa Alsharif; Faisal Alrehily; Fahad H Alhazmi; Awadia Greeballah; Abdulaziz A Qurashi; Shrooq Aldahery; Adnan Alahmadi; Amirah Alsaedi; Sultan Alshoabi; Khalid M Alshamrani; Awatif M Omer; Raghad Aljuhani (PLoS ONE)
Purpose To examine the current application of Evidence-Based Practice (EBP) among radiology professionals, including radiologists and radiographers, in Saudi Arabia and to identify challenges in order to propose suitable future improvement strategies if it is required. Method A mixed-method design was used in this study. A survey consisting of 23 questions addressing research activities and EBP within radiology departments was sent to radiology personnel. The sample size of the quantitative phase of the study was determined using a formula specific for an infinite or unknown population. The formula used was n = P(1-P)Z2/d2, which resulted in a required sample size of 384 participants. A total of 345 participants; however, 45 did not fully complete the questionnaire and were therefore excluded. The data were analyzed using SPSS version 27. Inferential statistics, including non-parametric tests such as the Mann-Whitney U Test and the Kruskal-Wallis Test, were used to assess the influence of demographic factors on perceptions and challenges related to the adoption of evidence-based practice (EBP) in research within Saudi Arabia. Additionally, 20 semi-structured interviews were conducted with radiology personnel across the country. The sampling technique for the qualitative phase of the study was guided by the study's objectives and the unique characteristics of the research group. The participants were purposively sampled in order to include radiologists and radiographers who work in different types of hospitals (public, semi-public, private) in Saudi Arabia. Responses from the interviews were coded, and key themes were identified following Miles and Huberman's framework. Results The findings revealed a positive attitude towards research and EBP among Saudi radiology personnel. Over half of the participants (74.3%) strongly agreed that they understood and were familiar with EBP. They also felt confident in their ability to conduct scientific research in radiology (Mean = 4.27) and believed that they should actively initiate projects (Mean = 4.10). Radiologists reported a higher level of agreement compared to radiographers regarding their familiarity with EBP and their ability to critically evaluate the quality of research (P-value = <0.05). However, participants indicated lower level of agreement about their ability to develop their current practice based on EBP and engage in discussions with colleagues about research evidence. Key challenges identified include a lack of training, insufficient support and limited autonomy, which may hinder EBP implementation. Conclusion This study underscores the need for comprehensive education, ongoing training and a supportive organisational culture to enhance EBP adaption.